2017
DOI: 10.1159/000455986
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Polymorphism of CARD8 rs2043211 and Susceptibility to Arteriosclerosis Obliterans in Chinese Han Male Population

Abstract: Background and aims: Cholesterol crystals have been shown to cause inflammation. As a response to cholesterol crystal accumulation, the NLRP3 inflammasome is activated to produce IL-1β which eventually leads to atherosclerotic lesions. As a part of innate immunity, CARD8 is involved in the modulation of above mentioned inflammatory activities. The primary objective of this study was to investigate the association between polymorphism of CARD8 rs2043211 and susceptibility to arteriosclerosis obliterans (ASO) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…On the contrary, carriers of the minor T allele of the CARD8 SNP rs2043211 also displayed lower circulating C‐reactive protein and lower levels of the pro‐atherosclerotic chemokine MCP‐1 . Despite the fact that there are contradictory results regarding the risk allele for the CARD8 SNP rs2043211, our results are in concordance with other authors reporting the T allele as the risk allele.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the contrary, carriers of the minor T allele of the CARD8 SNP rs2043211 also displayed lower circulating C‐reactive protein and lower levels of the pro‐atherosclerotic chemokine MCP‐1 . Despite the fact that there are contradictory results regarding the risk allele for the CARD8 SNP rs2043211, our results are in concordance with other authors reporting the T allele as the risk allele.…”
Section: Discussionsupporting
confidence: 90%
“…The SNP rs2043211 of CARD8 changes cysteine to a premature termination codon, thus yielding a truncated protein, which influences the protein function . Previous investigations have studied the relationship of the CARD8 SNP with different inflammatory diseases including cardiovascular disease: myocardial infarction , coronary atherosclerosis and also with ischemic stroke . However, conclusions are confusing and renal transplant recipients have never been studied in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP rs2043211 of CARD8 changes cysteine at codon10 to a premature termination codon, thus yielding a premature, truncated protein, which influences the protein function [38]. So far, more and more researches proved that the CARD8 SNP was associated with the increased risk of various cancers, such as nodular melanoma, hepatocellular carcinoma, and cervical cancer [3840]. In our study, we found that the AT genotype of CARD8-C10X (rs2043211) was associated with the increased risk of MM.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found to be associated with a lower expression of CARD8 in the plaque as well as with lower C-reactive protein and monocyte chemoattractant protein-1 levels in the plasma ( 8 , 15 , 16 ). However, in one Chinese cohort, rs2043211 was associated with ischemic stroke ( 10 ), and it is probably associated with the development of arteriosclerosis obliterans in the Chinese Han male population ( 11 ). Moreover, it has shown a modest protective effect against abdominal aortic aneurysms ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is encoded by exon 13 in 19q13, and it changes cysteine to a premature termination codon at codon 10, thus influencing the protein’s function in inflammasome-mediated processes and nuclear factor (NF)-κB suppression ( 8 , 9 ). Statistics have shown that CARD8 polymorphisms are related to the CVD risk ( 10 ), but several studies have reported different conclusions ( 8 , 11 , 12 ). Here, we present the first meta-analysis verifying the association between SNP rs2043211 in the CARD8 gene and CVDs.…”
Section: Introductionmentioning
confidence: 99%